MODEL DAN SIMULASI PERBANDINGAN PROTOTYPE RANGKAIAN DIGITAL HALF ADDER ALU STANDAR DENGAN INOVASI RANGKAIAN DIGITAL HALF ADDER ALU - Helmi Fauzi Siregar; Muhammad Dedi Irawan (Universitas Asahan, 2018)
Abstract - This research was conducted to model and simulate the Half Adder system. This system is designed by analyzing the descriptive method, and the comparative method. After analysis, modeling is done with UML (Unified Modeling Language) and hardware design based on microcontroller can be programmed using CodeVisionAVR-C software. The results of this study are a standard prototype Half ALU ALTER Adder system that uses XOR, AND, OR gates with ALU Half Adder system innovation using NAND and NOR gates.Keywords - Half Adder, Prototype, XOR, AND, OR, NAND, NOR